Pendekatan Tourism Business District dan Partisipatif dalam Pengembangan Jalur Wisata Perkotaan Kasus: Jalur Wisata Kota Jakarta - Winarso, Haryo; Oetomo, Andi; Priyani, Rina (Center for Research and Community Services ITB, 2003)
The products for market in urban tourism are heterogeneous; they range from products that show socio-economic diversity attractions, which is intangible to products such as souvenirs and historical artifacts as objects, which are tangible attractions. It is important to develop, products that can simultaneously offer the tangible and the intangible attractions to serve the market. . City sightseeing tour is one tourism products that linked the intangible and tangible attractions in one transportation route, therefore it enables tourists to choose objects and attractions they like to experience within their tight time/schedule. As a planning product, the city sightseeing route in Jakarta, is developed based on two approaches: Tourism Business District and Participatory. Tourism Business District Approach is chosen as it is optimize the utilization of all urban assets for public and tourism needs while the Participatory Approach may absorb the aspirations of stake holders . With those two approaches u is desired that the policy recommendations and/or the tourism activities for the city sightseeing route achieve the optimum outcomes.